High-hardness, high-toughness and high-refraction lanthanum aluminate glass as well as preparation method and application thereof

Through hafnium-doped lanthanum aluminate glass materials and specific preparation processes, the existing high-refractive index glass materials have been solved, and optical glass with high hardness, high toughness and high refractive index are prepared, which is suitable for electronic display and AR/VR technology.

CN119874188AActive Publication Date: 2025-04-25QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510056597.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-25
Estimated Expiration
2045-01-14

AI Technical Summary

Technical Problem

The existing high-refractive index glass materials have low hardness, poor toughness, toxic elements, and production technology limitations, which are difficult to meet the demand for high hardness, high toughness and high refractive index of electronic display technology.

Method used

Using hafnium-doped lanthanum aluminate glass material, high hardness, high toughness, high refractive lanthanum aluminate glass with refractive index above 2.0, high glass transition temperature and Vickers hardness are prepared through specific molar percentage composition and preparation processes, including high temperature calcination and dehydration, mechanical mixing, solvent mixing, sintering and laser melting.

Benefits of technology

It realizes high hardness, high toughness and high refractive index optical glass materials, suitable for electronic display lenses and windows, especially in the next generation of ultra-thin AR/VR technology and electronic imaging fields, and does not involve toxic components, and has good environmental protection and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119874188A_ABST
    Figure CN119874188A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of mid-infrared optical device materials, and particularly discloses high-hardness, high-toughness and high-refraction lanthanum aluminate glass and a preparation method and application thereof.The lanthanum aluminate glass is prepared from, by mole, 42-72 mol% of aluminum oxide, 20-58 mol% of lanthanum oxide and 1-22 mol% of hafnium oxide; the oxides are all analytically pure raw materials, and the purity is greater than 99.95%. According to the high-hardness, high-toughness and high-refraction lanthanum aluminate glass as well as the preparation method and the application thereof, novel hafnium-doped lanthanum aluminum series high-refraction optical glass is prepared, and the novel hafnium-doped lanthanum aluminum series high-refraction optical glass has the refractive index of 2.0 or above and also has relatively high glass transition temperature and Vickers hardness, so that the requirements of electronic display lenses and windows are met; therefore, the method can be applied to the next-generation ultrathin AR / VR technology and electronic imaging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of mid-infrared optical device materials, and in particular relates to a high-hardness, high-toughness, and high-refractive lanthanum aluminate glass, and a preparation method and application thereof. Background Art

[0002] In order to reduce the size of optical systems such as digital cameras, endoscopes and microscopes and reduce chromatic aberration, there is a great demand for optical glasses that combine high refractive index, low wavelength dispersion and high transparency over a wide wavelength range. As a core component of electronic display technology, high refractive index glass plays an indispensable role in the display system equipment of augmented reality (AR) and mixed reality (MR) devices, smartphones and military electronic reconnaissance display equipment. With the rapid development of electronic display technology, high refractive index glass above 2.0 provides key support for the brightness and clarity system of high-quality display systems with its effective light refraction performance. With the continuous selection of AR / VR technology, the demand for high refractive index glass has exploded. In the field of smartphones, high refractive index glass provides clear display effects for smartphones with its excellent optical and mechanical properties. Therefore, finding higher refractive index materials is of great significance to promote the development of AR technology.

[0003] At present, glasses with a refractive index higher than 2.0 generally contain a large amount of heavy metal oxides, such as PbO, Bi2O3, TeO2, etc. These elements often cause high-wavelength refraction and dispersion to present dark colors in the visible range, thus limiting their application. Secondly, glass materials generally have the disadvantages of low hardness and poor toughness, which greatly limits their use as electronic optical window materials that are in direct contact with relatively harsh external environments. Recent studies at home and abroad have shown that aluminate glass materials can significantly improve the hardness, mechanical properties and higher glass transition temperature of glass materials.

[0004] At present, the high-refractive glasses reported at home and abroad mainly include lead glass, tellurite glass, bismuth glass, lanthanum boron and their preparation methods. The above materials mainly contain toxic elements and involve problems such as volatility. In addition, due to the limitations of composition and preparation technology, the glass has low hardness and toughness, poor chemical stability, and poor composition melting uniformity, which has certain limitations when used as electronic display materials.

[0005] Therefore, the art needs to develop a high-hardness, high-toughness, high-refractive lanthanum aluminate glass and a preparation method and application thereof. By introducing hafnium elements, an optical glass with high hardness, high toughness, low phonon energy, high refractive index and good thermal stability can be obtained, which can effectively solve the above problems. Summary of the invention

[0006] The purpose of the present invention is to provide a high-hardness, high-toughness and high-refractive lanthanum aluminate glass and a preparation method and application thereof, to prepare a new type of hafnium-doped lanthanum-aluminum high-refractive optical glass, which has a refractive index of more than 2.0 and a high glass transition temperature and Vickers hardness to meet the needs of electronic display lenses and windows, so that it can be applied to the next generation of ultra-thin AR / VR technology and electronic imaging.

[0007] To achieve the above objectives, the present invention provides a high-hardness, high-toughness and high-refractive lanthanum aluminate glass, which comprises the following components by mole percentage: 42-72 mol% of aluminum oxide, 20-58 mol% of lanthanum oxide, and 1-22 mol% of hafnium dioxide; the oxides are all analytically pure raw materials with a purity greater than 99.95%.

[0008] Preferably, the high-hardness, high-toughness, high-refractive lanthanum aluminate glass has a Vickers hardness of 9.1-11.2 GPa, an indentation fracture resistance of 30-45N, a visible light transmittance of >85%, a refractive index n>2.02, and a transition temperature of >850°C.

[0009] A method for preparing high-hardness, high-toughness and high-refractive lanthanum aluminate glass comprises the following steps:

[0010] Step S1, preparing a uniformly mixed powder batch;

[0011] Step S2, placing the powdered batch material into a porous mold, filling each mold with 20-25 mg of the powdered batch material, setting the pressure to 20-25 MPa, and pressing the powdered batch material into a sheet-like block;

[0012] Step S3, placing the sheet block into a laser containerless pneumatic suspension furnace, turning on the upper carbon dioxide laser, adjusting the power to 50-60W, and the melting temperature to 2200-2500°C, and melting the sheet block into an irregular ceramic sphere sample; turning on the suspension gas, and at the same time turning on the lower carbon dioxide laser, adjusting the power to 40-50W;

[0013] Step S4, simultaneously adjusting the power of the upper and lower carbon dioxide lasers, turning on the airflow control system to allow the sample to complete resonance, making the sample temperature reach 2200-2500° C., stabilizing the airflow and laser system for 2 minutes to ensure that the entire sample is melted evenly;

[0014] Step S5, quickly turning off the carbon dioxide laser at the resonance frequency, and quickly cooling the sample to obtain a high-hardness, high-toughness, and high-refractive lanthanum aluminate glass sample;

[0015] Step S6, placing the high-hardness, high-toughness, high-refractive lanthanum aluminate glass sample in an annealing furnace for annealing treatment, the annealing temperature is 840° C., the annealing time is 2 hours, and the high-hardness, high-toughness, high-refractive lanthanum aluminate glass is obtained by cooling in the furnace.

[0016] Preferably, step S1 specifically comprises:

[0017] Step S11, subjecting aluminum oxide, lanthanum oxide, and hafnium dioxide to a high-temperature calcination dehydration treatment at 700° C. for 2 hours to reduce the moisture and hydroxyl content of the glass raw materials;

[0018] Step S12, weighing powders according to the molar percentage composition of 42-72 mol% of aluminum oxide, 20-58 mol% of lanthanum oxide, and 1-22 mol% of hafnium dioxide, and ball milling to obtain original powders;

[0019] Step S13, adding an appropriate amount of alcohol dispersion medium to the original powder to obtain a mixture A; then placing the mixture A on a magnetic stirrer and stirring it for 1-2 hours to obtain a uniformly mixed mixture B;

[0020] Step S14, drying the mixed material B for a second time at 500° C. to obtain a dried mixed material B;

[0021] Step S15, adding polyvinyl alcohol to the dried mixture B and performing magnetic stirring for 2-3 hours to obtain a mixture C; after stirring, sintering the mixture C at 1200° C. to remove the polyvinyl alcohol in the mixture C and obtain a uniformly mixed powder batch.

[0022] Preferably, the heating rate of the high temperature calcination in step S11 and the sintering in step S15 is 5-10° C. / min.

[0023] Preferably, in step S2, the pressing time is 5 to 10 minutes.

[0024] Preferably, in step S3, the gas used in the pneumatic suspension furnace is air; ensuring that the upper laser power / lower laser power is 1.2-1.5.

[0025] Preferably, in step S5, the cooling rate is 500-1000°C / S.

[0026] A method for preparing high-hardness, high-toughness and high-refractive lanthanum aluminate glass and application of the prepared high-hardness, high-toughness and high-refractive lanthanum aluminate glass in imaging systems and electronic components.

[0027] The present invention adopts the above-mentioned high-hardness, high-toughness and high-refractive lanthanum aluminate glass and its preparation method and application, and the beneficial effects are as follows:

[0028] (1) The high-hardness, high-toughness and high-refractive lanthanum aluminate glass prepared by the present invention has excellent transmittance in the visible light region and the near-mid-infrared band, and can be made into electronic optical devices with excellent mechanical properties and good transmittance after grinding and polishing;

[0029] (2) The high-hardness, high-toughness and high-refractive lanthanum aluminate glass prepared by the present invention has good mechanical properties. Experiments have shown that the introduction of hafnium oxide can significantly improve the hardness of the glass, and it has excellent anti-crystallization performance, thermal shock resistance and erosion resistance;

[0030] (3) The high-hardness, high-toughness and high-refractive lanthanum aluminate glass prepared by the present invention does not involve toxic components such as fluorine, chlorine, sulfur and lead during the preparation process, and has good environmental safety;

[0031] (4) The high-hardness, high-toughness and high-refractive lanthanum aluminate glass (10 mm thick) prepared by the present invention has the following characteristics: transmittance ≥ 80% in the visible light region (800-2800 nm); refractive index ≥ 2.2, hardness ≥ 9.1 MPa; softening temperature ≥ 850°C, water resistance stability of level III, and toughness ≥ 30N.

[0032] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 A high-hardness, high-toughness, high-refractive lanthanum aluminate glass and a preparation method and application example 1 of the present invention, and a resonance shift curve of the lanthanum aluminate melt;

[0034] Figure 2 The cooling curve diagram of the glass in the first embodiment of the present invention, a lanthanum aluminate glass with high hardness, high toughness and high refractive index and a preparation method thereof, and a cooling curve diagram of a standard sample of aluminum oxide;

[0035] Figure 3 The X-ray diffraction spectrum of the glass in Example 1 of the high-hardness, high-toughness and high-refractive lanthanum aluminate glass and its preparation method and application;

[0036] Figure 4 A DSC graph of the glass in Example 1 of the present invention for a lanthanum aluminate glass with high hardness, high toughness and high refractive index and a preparation method thereof and application thereof;

[0037] Figure 5 A refractive index curve of the glass in Example 1 of the present invention, a lanthanum aluminate glass with high hardness, high toughness and high refractive index, a preparation method thereof and an application thereof;

[0038] Figure 6 This is a microscopic indentation image of the glass at 50N in Example 1 of the high-hardness, high-toughness and high-refractive lanthanum aluminate glass and its preparation method and application;

[0039] Figure 7 This is a transmission spectrum diagram of the glass in Example 1 of the high-hardness, high-toughness and high-refractive lanthanum aluminate glass and its preparation method and application. DETAILED DESCRIPTION

[0040] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.

[0041] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.

[0042] Embodiment 1

[0043] A high-hardness, high-toughness and high-refractive lanthanum aluminate glass, comprising the following steps:

[0044] Step S1, preparing a uniformly mixed powder batch material through primary mechanical mixing and secondary solvent mixing.

[0045] Step S11, subjecting aluminum oxide, lanthanum oxide, and hafnium dioxide to a high-temperature calcination dehydration treatment at 700° C. for 2 hours to reduce the moisture and hydroxyl content of the glass raw materials.

[0046] Step S12, weighing 12 mol% of hafnium dioxide (HfO2), 30 mol% of lanthanum oxide (La2O3), and 58 mol% of aluminum oxide (Al2O3) in a molar percentage composition ratio as high-purity batch materials, and ball-milling to obtain original powder.

[0047] Step S13, the original compound powder is placed in an alumina crucible, and an appropriate amount of alcohol dispersion medium is added to the original powder to obtain a mixture A. Then the mixture A is placed on a magnetic stirrer and stirred for 2 hours to obtain a uniformly mixed mixture B.

[0048] Step S14, placing the mixed material B in a glass furnace at 500° C. and heating for 2 hours for secondary drying to obtain a dried mixed material B.

[0049] Step S15, adding polyvinyl alcohol to the dried mixed material B and performing magnetic stirring for 2 hours to obtain mixed material C. After stirring, the mixed material C is sintered at 1200° C. for 2 hours to remove impurities and organic solvents in the mixed material C to obtain a uniformly mixed powder batch.

[0050] Step S2: Put the powdered batch into a stainless steel porous mold, fill each mold with 25 mg of the powdered batch, set the pressure to 20 MPa, and press the powdered batch into a sheet-like block.

[0051] Step S3, placing the sheet block into a laser containerless pneumatic suspension furnace, turning on the upper carbon dioxide laser, adjusting the power to 50W, and the melting temperature to 2500°C, to melt the sheet block into an irregular ceramic sphere sample. Turning on the suspension gas, turning on the lower carbon dioxide laser at the same time, and adjusting the power to 40W.

[0052] Step S4, simultaneously adjusting the power of the upper and lower carbon dioxide lasers, turning on the airflow control system to allow the sample to complete resonance, making the sample temperature reach 2200° C., stabilizing the airflow and laser system for 2 minutes to ensure that the entire sample melts evenly.

[0053] Step S5: Figure 1 As shown, the CO2 laser is quickly turned off at the resonant frequency, such as Figure 2 As shown, the sample is rapidly cooled at 500-1000°C / S to obtain a high-hardness, high-toughness, and high-refractive lanthanum aluminate glass sample, wherein the sample diameter is 3 mm.

[0054] Step S6, placing the high-hardness, high-toughness, high-refractive lanthanum aluminate glass sample in an annealing furnace for annealing treatment, the annealing temperature is 840° C., the annealing time is 2 hours, and the high-hardness, high-toughness, high-refractive lanthanum aluminate glass is obtained by cooling in the furnace.

[0055] The high hardness, high toughness and high refractive index lanthanum aluminate glass prepared in this embodiment was first subjected to XRD test. Figure 3 As shown in the figure, the sample has no crystallization peak, proving that the prepared sample is a glass sample. Secondly, the high-hardness, high-toughness, and high-refractive lanthanum aluminate glass was subjected to DSC thermal analysis test. The DSC curve of the glass is shown in Figure 4 As shown in Figure 1, the transition temperature Tg of the high-hardness, high-toughness and high-refractive lanthanum aluminate glass is 861°C, and the crystallization start temperature Tx is 993°C. The Vickers hardness is 9.57GPa, and the fracture resistance is 35N. Figure 5 As shown. The refractive index of the high-hardness, high-toughness, high-refractive lanthanum aluminate glass is 2.02. The visible light transmittance of the high-hardness, high-toughness, high-refractive lanthanum aluminate glass is greater than 80%.

[0056] Embodiment 2

[0057] Step S1, preparing a uniformly mixed powder batch material.

[0058] Step S11, subjecting aluminum oxide, lanthanum oxide, and hafnium dioxide to a high-temperature calcination dehydration treatment at 700° C. for 2 hours to reduce the moisture and hydroxyl content of the glass raw materials.

[0059] Step S12, weighing 22 mol% of hafnium dioxide (HfO2), 20 mol% of lanthanum oxide (La2O3), and 58 mol% of aluminum oxide (Al2O3) in a molar percentage composition ratio as high-purity batch materials, and ball-milling to obtain original powder.

[0060] Step S13, the original compound powder is placed in an alumina crucible, and an appropriate amount of alcohol dispersion medium is added to the original powder to obtain a mixture A. Then the mixture A is placed on a magnetic stirrer and stirred for 2 hours to obtain a uniformly mixed mixture B.

[0061] Step S14, placing the mixed material B in a glass furnace at 500° C. and heating for 2 hours for secondary drying to obtain a dried mixed material B.

[0062] Step S15, adding polyvinyl alcohol to the dried mixed material B and performing magnetic stirring for 2 hours to obtain mixed material C. After stirring, the mixed material C is sintered at 1200° C. for 2 hours to remove impurities and organic solvents in the mixed material C to obtain a uniformly mixed powder batch.

[0063] Step S2: Put the powdered batch material into a stainless steel porous mold, fill each mold with 20 mg of the powdered batch material, set the pressure to 20 MPa, and press the powdered batch material into a sheet-like block.

[0064] Step S3, placing the sheet block into a laser containerless pneumatic suspension furnace, turning on the upper carbon dioxide laser, adjusting the power to 60W, and the melting temperature to 2500°C, to melt the sheet block into an irregular ceramic sphere sample. Turning on the suspension gas, turning on the lower carbon dioxide laser at the same time, and adjusting the power to 50W.

[0065] Step S4, simultaneously adjusting the power of the upper and lower carbon dioxide lasers, turning on the airflow control system to allow the sample to complete resonance, making the sample temperature reach 2500° C., stabilizing the airflow and laser system for 2 minutes to ensure that the entire sample is melted evenly.

[0066] Step S5, quickly turn off the carbon dioxide laser at the resonant frequency, and quickly cool the sample at 500-1000°C / S to obtain a high-hardness, high-toughness, and high-refractive lanthanum aluminate glass sample, wherein the sample diameter is 3 mm.

[0067] Step S6, placing the high-hardness, high-toughness, high-refractive lanthanum aluminate glass sample in an annealing furnace for annealing treatment, the annealing temperature is 845° C., the annealing time is 2 hours, and the high-hardness, high-toughness, high-refractive lanthanum aluminate glass is obtained by cooling in the furnace.

[0068] The high-hardness, high-toughness, high-refractive lanthanum aluminate glass prepared in this embodiment is first subjected to an XRD test. The sample has no crystallization peak, proving that the prepared sample is a glass sample. Next, the high-hardness, high-toughness, high-refractive lanthanum aluminate glass is subjected to a DSC thermal analysis test. The transition temperature Tg of the lanthanum aluminate glass is 869°C, the crystallization start temperature Tx is 1003°C, the Vickers hardness is 9.97 GPa, the fracture resistance is 39N, and the refractive index of the lanthanum aluminate glass is 2.12. Figure 6 The high hardness, high toughness and high refractive index lanthanum aluminate glass prepared in this embodiment has a visible light transmittance of more than 80%. Figure 7 shown.

[0069] Therefore, the present invention adopts the above-mentioned high-hardness, high-toughness and high-refractive lanthanum aluminate glass and its preparation method and application to prepare a new type of hafnium-doped lanthanum aluminum high-refractive optical glass, which has a refractive index of more than 2.0 and a high glass transition temperature and Vickers hardness to meet the needs of electronic display lenses and windows, so that it can be applied to the next generation of ultra-thin AR / VR technology and electronic imaging.

[0070] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A high-hardness, high-toughness and high-refractive lanthanum aluminate glass, characterized in that: The invention comprises the following components in molar percentage: 42-72 mol% of aluminum oxide, 20-58 mol% of lanthanum oxide and 1-22 mol% of hafnium dioxide; all the oxides are analytically pure raw materials with a purity greater than 99.95%.

2. The high-hardness, high-toughness, high-refractive lanthanum aluminate glass according to claim 1, characterized in that: The Vickers hardness of the high-hardness, high-toughness and high-refractive lanthanum aluminate glass is 9.1-11.2GPa, the indentation fracture resistance is 30-45N, the visible light transmittance is >85%, the refractive index n is >2.02, and the transition temperature of the high-hardness, high-toughness and high-refractive lanthanum aluminate glass is >850°C.

3. A method for producing high-hardness, high-toughness and high-refractive lanthanum aluminate glass according to any one of claims 1 to 2, characterized in that: The following steps are involved: Step S1, preparing a uniformly mixed powder batch; Step S2, placing the powdered batch material into a porous mold, filling each mold with 20-25 mg of the powdered batch material, setting the pressure to 20-25 MPa, and pressing the powdered batch material into a sheet-like block; Step S3, placing the sheet block into a laser containerless pneumatic suspension furnace, turning on the upper carbon dioxide laser, adjusting the power to 50-60W, and the melting temperature to 2200-2500°C, and melting the sheet block into an irregular ceramic sphere sample; turning on the suspension gas, and at the same time turning on the lower carbon dioxide laser, adjusting the power to 40-50W; Step S4, simultaneously adjusting the power of the upper and lower carbon dioxide lasers, turning on the airflow control system to allow the sample to complete resonance, making the sample temperature reach 2200-2500° C., stabilizing the airflow and laser system for 2 minutes to ensure that the entire sample is melted evenly; Step S5, quickly turning off the carbon dioxide laser at the resonance frequency, and quickly cooling the sample to obtain a high-hardness, high-toughness, and high-refractive lanthanum aluminate glass sample; Step S6, placing the high-hardness, high-toughness, high-refractive lanthanum aluminate glass sample in an annealing furnace for annealing treatment, the annealing temperature is 840° C., the annealing time is 2 hours, and the high-hardness, high-toughness, high-refractive lanthanum aluminate glass is obtained by cooling in the furnace.

4. The method for preparing a high-hardness, high-toughness and high-refractive lanthanum aluminate glass according to claim 3, characterized in that: Step S1 specifically comprises: Step S11, subjecting aluminum oxide, lanthanum oxide, and hafnium dioxide to a high-temperature calcination dehydration treatment at 700° C. for 2 hours to reduce the moisture and hydroxyl content of the glass raw materials; Step S12, weighing powders according to the molar percentage composition of 42-72 mol% of aluminum oxide, 20-58 mol% of lanthanum oxide, and 1-22 mol% of hafnium dioxide, and ball milling to obtain original powders; Step S13, adding an appropriate amount of alcohol dispersion medium to the original powder to obtain a mixture A; then placing the mixture A on a magnetic stirrer and stirring it for 1-2 hours to obtain a uniformly mixed mixture B; Step S14, drying the mixed material B for a second time at 500° C. to obtain a dried mixed material B; Step S15, adding polyvinyl alcohol to the dried mixture B and performing magnetic stirring for 2-3 hours to obtain a mixture C; after stirring, sintering the mixture C at 1200° C. to remove the polyvinyl alcohol in the mixture C and obtain a uniformly mixed powder batch.

5. The method for preparing a high-hardness, high-toughness and high-refractive lanthanum aluminate glass according to claim 4, characterized in that: The heating rates of high temperature calcination in step S11 and sintering in step S15 are 5-10° C. / min.

6. The method for preparing a high-hardness, high-toughness and high-refractive lanthanum aluminate glass according to claim 3, characterized in that: In step S2, the pressing time is 5 to 10 minutes.

7. The method for preparing a high-hardness, high-toughness and high-refractive lanthanum aluminate glass according to claim 3, characterized in that: In step S3, the gas used in the pneumatic suspension furnace is air; it is ensured that the upper laser power / lower laser power is 1.2-1.

5.

8. The method for preparing a high-hardness, high-toughness and high-refractive lanthanum aluminate glass according to claim 3, characterized in that: In step S5, the cooling rate is 500-1000°C / S.

9. Application of high-hardness, high-toughness, high-refractive lanthanum aluminate glass prepared by the method for preparing high-hardness, high-toughness, high-refractive lanthanum aluminate glass as described in any one of claims 3 to 8 in imaging systems and electronic components.

Citation Information

Patent Citations

  • High-strength, high-toughness and high-refractive-index miniature glass ceramic lens and preparation method thereof

    CN111217529A

  • High-refractive-index and high-hardness glass material and preparation method thereof

    CN115180827A

  • Aluminum-tantalum oxide glass with high hardness, high Young modulus and ultrahigh refractive index as well as preparation method and application of aluminum-tantalum oxide glass

    CN116282912A

  • Method for preparing large-size transparent YAG nano ceramic through amorphous crystallization

    CN117229047A

  • Quartz-type glass and its production method

    JP2006306705A